Nano-enabled pancreas cancer immunotherapy using immunogenic cell death and reversing immunosuppression. Issue 1 (December 2017) - Lu, Jianqin; Liu, Xiangsheng; Liao, Yu-Pei; Salazar, Felix; Sun, Bingbing; Jiang, Wen; Chang, Chong; Jiang, Jinhong; Wang, Xiang; Wu, Anna; Meng, Huan; Nel, Andre
Abstract While chemotherapy delivery by nanocarriers has modestly improved the survival prospects of pancreatic ductal adenocarcinoma (PDAC), additional engagement of the immune response could be game changing. We demonstrate a nano-enabled approach for accomplishing robust anti-PDAC immunity in syngeneic mice through the induction of immunogenic cell death (ICD) as well as interfering in the immunosuppressive indoleamine 2, 3-dioxygenase (IDO) pathway. This is accomplished by conjugating the IDO inhibitor, indoximod (IND), to a phospholipid that allows prodrug self-assembly into nanovesicles or incorporation into a lipid bilayer that encapsulates mesoporous silica nanoparticles (MSNP). The porous MSNP interior allows contemporaneous delivery of the ICD-inducing chemotherapeutic agent, oxaliplatin (OX). The nanovesicles plus free OX or OX/IND-MSNP induce effective innate and adaptive anti-PDAC immunity when used in a vaccination approach, direct tumor injection or intravenous biodistribution to an orthotopic PDAC site. Significant tumor reduction or eradication is accomplishable by recruiting cytotoxic T lymphocytes, concomitant with downregulation of Foxp3+ T cells. Pancreatic cancer remains difficult to treat mainly due to the drug delivery challenges posed by a strong stromal component. Here the authors develop nanocarriers that improve drug delivery efficiency and engage the host immune system against the tumor resulting in reduction of tumor growth and metastasis.